An Effective Key Management Protocol on AODV for Group Security - Sharma , Bhawna; Vaid , Rohit (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Mobile Ad Hoc Networks, or MANETs, are decentralised networks made up of mobile devices that can connect with one another without the use of a centralised infrastructure. Because MANETs are dynamic and self-organizing, securing data transfer presents specific difficulties, particularly with regard to routing algorithms. By providing authentication and confidentiality for communication among the participating nodes, the Key Management Protocol for MANET Routing Group Security is a protocol created to secure the routing operations within a MANET. In this study, group communication security is provided using a combination of the RSA and DH (Diffie-Hellman) algorithms. Utilizing metrics like routing overhead, throughput, and security level, the performance of this ensemble key management system is evaluated for the AODV. After using this technique, we discovered that our suggested ensemble method secures group communication as compared to Diffie-Hellman, improves throughput by altering the quantity of messages sent, and decreases routing overhead in various groups. Group security over Diffie-Hellman was boosted by 30% by combining RSA and DH.